HUBUNGAN STATUS GIZI, TINGKAT ASUPAN ENERGI, BEBAN KERJA DENGAN PRODUKTIVITAS PEKERJA WANITA DI PERUSAHAAN BAUT DAN MUR: Relationship of Nutrition Status, Energy Intake Level, Workload with Productivity of Female Worker in Bolt and Nut Manufacturer - Melda Monisca Butar; Triska Susila Nindya (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2018)
ABSTRACT Women's participation in employment increases from year to year, due to the increasing number of industries requiring women's skills. The health of women workers should be of special concern in order to increase productivity. This study aims was to analyze the relationship of nutritional status, the level of energy intake, the workload with the productivity of female workers part of the packaging. This research was observational analytic with cross-sectional study design. This research was conducted in PT X, the sample size of this research was all female worker population of packaging with 35 people. Data were collected by measuring height, body weight, pulse rate, and 2 x 24 hour food recall interview. The analysis data using contingency coefficient test to see strenght relationship between varibael. The results of this research were female employee with characteristics most of the age group of 30-49 years, mostly elementary school graduates, most of them were married, and more than five years of service. The results showed that value of contingeny coefficient was nutrition status (0.458), energy intake level (0.388), and work load (0.341). Of the three variable was only nutritional status with moderate stregth relationship, while the level of energy intake level and the workload had a weak stregth relationship. It can be concluded that productivity among female worker in PT X is more affected by nutritional status compared energy intake level and work load. Companies are advised to providing canteen, providing counseling on balanced nutrition, and exercise activity.